2020
DOI: 10.3389/fmicb.2020.01382
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mitogenome Analysis Reveals Mitochondrial Genome Differentiation in Ectomycorrhizal and Asymbiotic Amanita Species

Abstract: In this present study, we assembled and analyzed the mitogenomes of two asymbiotic and six ectomycorrhizal Amanita species based on next-generation sequencing data. The size of the eight Amanita mitogenomes ranged from 37,341 to 137,428 bp, and we considered introns to be one of the main factors contributing to the size variation of Amanita. The introns of the cox1 gene experienced frequent gain/loss events in Amanita; and the intron position class cox1P386 was lost in the six ectomycorrhizal Amanita species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…However, the mitogenomes of fungi have been less studied than those of animals. Up to now, few mitochondrial molecular markers have been employed in studying their population genetics or phylogeny (Li et al 2020 ). We obtained identical and well-supported tree topologies by BI and ML revealing phylogenetic relationships amongst 61species of Basidiomycota , based on the combined mitochondrial gene set.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mitogenomes of fungi have been less studied than those of animals. Up to now, few mitochondrial molecular markers have been employed in studying their population genetics or phylogeny (Li et al 2020 ). We obtained identical and well-supported tree topologies by BI and ML revealing phylogenetic relationships amongst 61species of Basidiomycota , based on the combined mitochondrial gene set.…”
Section: Discussionmentioning
confidence: 99%
“…The few mitogenomes available limited our comprehensive understanding of the origin and evolution of Basidiomycota. With the rapid development of the next generation sequencing (NGS) technology, more and more fungal mitogenomes obtained (Li et al 2020a ), which promotes further development of fungal taxonomy and phylogeny.…”
Section: Introductionmentioning
confidence: 99%
“…The phylum Basidiomycota is the largest group of mushroom-forming fungi on earth. Analysis of Basidiomycota mitogenomes will help us to understand the origin and evolution of mushrooms ( Li et al, 2020a ). Previous studies have shown that the evolution rate of fungal mitogenome was intermediate between animals (the highest) and plants (the lowest) ( Aguileta et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%